Gambaran Psikologis Cinderella Complex Syndrome Pada Perempuan Suku Banjar (Studi Deskriptif Pada KAMMI Kota Banjarmasin) - Nurhafizah, Ayu; Faridah, Siti; Imadduddin, Imadduddin (Jurnal Al-Husna, 2020)
The cinderella complex syndrome is a network of attitudes and fears in women and makes them feel depressed, causing fearness to use their ability, thus their desire to always be taken care of and protected appeared. The purpose of this research is to know the psychological description of cinderella complex syndrome in women who joined KAMMI Banjarmasin which includes the forming process, factors, characteristics, and aspects. This is field research with descriptive qualitative approach in Banjarmasin with 2 subjects aged 20 and 21 years old. The data collecting methods used in this research is screening test using the scale of the cinderella complex syndrome, interviews, observation, and graphic tests (with analysis results of the tests that supervised by a psychologist). The result of this research indicates that the forming process of the cinderella complex syndrome is closely related to various childhood experiences. The influencing factors are culture, parenting, mass media, low self-esteem, and perception. The characteristics that apparent are lack of confidence, feel worthless, afraid to face challenges, hard to do everything by herself, often having psychosomatic, fear of failure, lazy to take a risk, and dependent. Aspects that seen are they expect directions from others, external self-control, low self-esteem, avoid challenges, and competitions. There are also aspects of emotions, cognitive, and social that has been successfully revealed through graphic test.